Marginal Land Suitability Study At Hillside Pomarak For Plant Cocoa (Theobroma cacao) in Nagari Kinari Bukit Sundi District of Solok District - Yasri, Salmira - (STKIP PGRI Sumbar, 2014)
The purpose of this research is learning, reveal, analyze and interpret data about appropriate the physical condition of the soil (texture, struktur, drainage) and chemical (pH and organic) and rainfall at marginal land for cacao plant. The method used is descriptive. Method of soil sampling in this research is based on 3 samples with land cover and slope. The sample is marginal of land area that there in slope of Pomarak Kanagarian Kinari Bukit Sundi District of Solok district. Results of laboratory research and analysis is obtained as follows: 1) At the top of the sample obtained 3 textures in the texture of sand fraction of 5.38%, 40.80% of dust, clay loam texture class 54.54% dust (silt, clay / Si, Cl) , (t3: medium), structure-grained soil with a bad grade, drainage rather good (d1), pH 5.38 with a rather sour grade, and class materials are orgaik 4.103%, the sample used is in accordance with the structure of cocoa cultivation as a factor barrier. 2) In the Middle point 8.77% is obtained textures of sand, dust 34.16%, 57.07% with grade clay loam texture (clay / Cl), (t3: medium), soil structure class pole with a rather bad, good drainage (d0), pH 5.64 with a slightly sour grade, and organic matter 2.965% lower class, on this sample used as suitable for the cultivation of cocoa and a good park for growth. 3) At what point is obtained textures Foot sand 7.06%, 32.93% of dust, clay loam texture class 60.01 (clay / Cl), (t3: medium), blocky soil structure by class rather good, well drained (d0), pH 5.50 with class rather sour, and the organic material was 4.379% class, the sample is suitable for the cultivation of cocoa used as blocky soil structure. 4) The amount of annual rainfall in the study area is 1081 mm / yr, due to the high rainfall is suitable for cocoa plants.